Inflation: Essence, Types, Measurement, Social-Economical Consequences - N. Y. Kazhuro (Наука и техника)
The paper reveals the essence of an inflation as a macro-economical process embracing the whole country’s economy. Reasons of its origin, methods of its measurement and social-economical consequences for various groups of population and society as a whole are analyzed in the paper.